Malicious Node Detection in Wireless Sensor Networks using Cryptographic Authentication and Certificate Revocation Mechanism - TC, Swetha Priya; A, Kanaka Durga (International Journal of Computer Sciences and Engineering, 2019)
Security is one of the major issues in the current scenario. Because of the wireless nature of the nodes present in Wireless Sensor Networks, there is a chance of the nodes getting easily affected to severe security attacks. One such attack is a Selective Forwarding Attack in which the malicious nodes gain access to the wireless network and interrupts the data communication, overwrites the data packets, drops the packets and degrades the wireless network performance. In this paper, an effective cryptographic protocol using Authentication technique is proposed. To separate the attacking nodes in participating in the future networking activities, a Certificate Revocation Method is also proposed. This paper guarantees security to the nodes and do not allow access to any of the affected nodes by using a more efficient Authentication method. It also improves the performance of a network. Through simulation, the correctness and efficiency of the scheme is verified.